West Nile Virus Capsid Protein Interacts With Biologically Relevant Host Lipid Systems - Martins, Ana S.; Carvalho, Filomena A.; Faustino, André F.; Martins, Ivo C.; Santos, Nuno C. (Frontiers in Cellular and Infection Microbiology, 2019)
West Nile and dengue viruses are closely related flaviviruses, originating mosquito-borne viral infections for which there are no effective and specific treatments. Their capsid proteins sequence and structure are particularly similar, forming highly superimposable α-helical homodimers. Measuring protein-ligand interactions at the single-molecule level yields detailed information of biological and biomedical relevance. In this work, such an approach was successfully applied on the characterization of the West Nile virus capsid protein interaction with host lipid systems, namely intracellular lipid droplets (an essential step for dengue virus replication) and blood plasma lipoproteins. Dynamic light scattering measurements show that West Nile virus capsid protein binds very-low density lipoproteins, but not low-density lipoproteins, and this interaction is dependent of potassium ions. Zeta potential experiments show that the interaction with lipid droplets is also dependent of potassium ions as well as surface proteins. The forces involved on the binding of the capsid protein with lipid droplets and lipoproteins were determined using atomic force microscopy-based force spectroscopy, proving that these interactions are K+-dependent rather than a general dependence of ionic strength. The mode of capsid protein interaction with host lipid systems may be used as drug target for future therapeutic strategies against different flaviviruses. The biophysical and nanotechnology approaches employed in this study may be applied to characterize the interactions of other important proteins from different viruses, in order to understand their life cycles, as well as to find new strategies to inhibit them.